1998
DOI: 10.1146/annurev.physiol.60.1.309
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Abnormal Consequences of Apoptosis in the Human Heart

Abstract: Knowledge about apoptosis has become essential for understanding many aspects of cardiac structure and function. In the human heart there are major periods of morphogenesis that begin only after birth, and some of these processes recur intermittently for many years. Although the exact mechanisms by which these events are initiated or terminated remain poorly understood, it is clear that their benefits may be mirrored in destructive effects. In this review, selected examples include normal morphogenesis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 70 publications
1
60
0
2
Order By: Relevance
“…This is what James first referred as ''molding and shaping'' of the atrio-ventricular (AV) node and His bundle, a process never claimed as unique to crib death but that, on the contrary, must be considered a normal postnatal morphological change [10,17,18]. This postnatal morphogenesis is mediated by apoptotic death of myocytes in both the sinus node and the AV junctional tissue [39,40]. Since there is no associated inflammation or other indicators of necrosis, some authors have considered such changes as normal or harmless.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This is what James first referred as ''molding and shaping'' of the atrio-ventricular (AV) node and His bundle, a process never claimed as unique to crib death but that, on the contrary, must be considered a normal postnatal morphological change [10,17,18]. This postnatal morphogenesis is mediated by apoptotic death of myocytes in both the sinus node and the AV junctional tissue [39,40]. Since there is no associated inflammation or other indicators of necrosis, some authors have considered such changes as normal or harmless.…”
Section: Discussionmentioning
confidence: 94%
“…The programmed cell death named apoptosis is of particular interest [98 -102]; its unpredictable occurrence could play a role in the pathogenesis of crib death [10,40,51,98]. Matturri et al [98], in a study on eight crib death and three control hearts, found that the apoptotic indices (AI) in AV node, His bundle, bundle branches, did not to have statistically significant differences ( P>0.05), while in the resorptive degeneration areas the AI resulted higher in control than crib death group.…”
Section: Apoptosis Of the Cardiac Conduction Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation of Uhl's anomaly is that the right ventricular myocardium undergoes selective apoptosis in utero 9 10 Apoptosis is a type of cell death that is considered a normal phenomenon in postnatal heart maturation 9 . The excessive right ventricular myocardial mass is reduced via apoptosis due to the reduction of the pressure against the right ventricle after birth 11 .…”
Section: Discussionmentioning
confidence: 99%